Estudo teórico-experimental de compostos Cage-Like com potencial atividade biológica: um estudo por ressonância magnética nuclear - Barbosa, Layla Rosario (2013)
This study analyzed four cage-like rigid polycyclic compounds obtained from a DielsAlder adduct deriving from the reaction between para-benzoquinone and cyclopentadiene. The NMR spectra of these compounds were analyzed employing unidimensional techniques (1H NMR, 13C NMR, DEPT-135) and bidimensional (COSY, HMBC, HSQC and NOESY). The experimental data obtained from the attribution of chemical displacement values of 1H NMR and 13C NMR and spin-spin coupling (J) were compared with theoretical data obtained through computational calculations, which analyzed the standard mean deviation (MD), standard deviation (SD) and linear correlation coefficient (R) for the endo and exo adducts of each compound. Systematic studies were carried out in order to validate de efficiency of the solvent effect during the optimization stage (comparing two different calculation routines) and to evaluate which method – GIAO or CSGT – showed better correlation with the experimental data. Also, the study evaluated if model B3LYP/cc-pVTZ showed good results during the shielding tensor (s) calculation and spin-spin coupling (J) constant calculation. In all the experiments, the mean deviation, standard deviation, and linear correlation coefficient values were better for the endo adduct compared to the exo adduct. Large differences were observed for the 1H NMR values of compound 15. In this case, the mean deviation value of exo adduct was about 9 times bigger than the mean deviation of the endo adduct. Likewise, the standard deviation value was 6 times bigger for the exo adduct compared to endo. Based on the correlation between theoretical and experimental data, it was possible to unmistakably attribute the NMR signals of the study compounds. We can also conclude that the model used (B3LYP/cc-pVTZ) was efficient to calculate the shielding tensors and coupling constant, and that the compounds analyzed correspond to the endo adduct. When analyzing the solvent efficiency during the optimization stage (comparing Routines 1 and 2), we concluded that Routine 2 (which disregards solvent effect) showed to be effective to describe the chemical displacements of 13C NMR and 1H NMR and the coupling constants JH,H, which are associated to lower computational costs. If both methods for NMR property calculation are compared, we can conclude that CSGT was effective to describe the chemical displacements of 13C NMR and 1H NMR, which are associated to higher cost-effectiveness.